2019
DOI: 10.7717/peerj.7852
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dengue cases among patients with an acute illness, Central Department, Paraguay

Abstract: Background In 2018, Paraguay experienced a large dengue virus (DENV) outbreak. The primary objective of this study was to characterize dengue cases in the Central Department, where the majority of cases occur, and identify factors associated with DENV infection. Methods Patients were enrolled from January-May 2018 if they presented with a suspected arboviral illness. Acute-phase specimens (≤8 days after symptom onset) were tested using rRT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 49 publications
1
35
0
3
Order By: Relevance
“…These findings are similar to our report, where all of the malarial cases had anemia and splenomegaly on admission. Rojas A et al 23 found headache, red eyes, leucopenia, and thrombopenia commoner in dengue compared to other febrile illnesses similar to our study. There have been recent efforts to develop testing kits for simultaneous detection of viral infections that are in close differentials from each other 24,25 …”
Section: Discussionsupporting
confidence: 91%
“…These findings are similar to our report, where all of the malarial cases had anemia and splenomegaly on admission. Rojas A et al 23 found headache, red eyes, leucopenia, and thrombopenia commoner in dengue compared to other febrile illnesses similar to our study. There have been recent efforts to develop testing kits for simultaneous detection of viral infections that are in close differentials from each other 24,25 …”
Section: Discussionsupporting
confidence: 91%
“…El DENV corresponde al género Flavivirus de la familia Flaviviridae, con cuatro serotipos filogenética y antigénicamente distintos (DENV-1, DENV-2, (2,3) DENV-3 y DENV-4) . La infección por DENV tiene un amplio espectro de presentaciones clínicas pudiendo causar desde infección subclínica a formas graves con choque y complicaciones (4) (hemorragias, hepatitis, miocarditis, encefalitis) .…”
Section: Introductionunclassified
“…4 Rapid diagnostics are available for the detection of DENV nonstructural protein 1 (NS1) and anti-DENV IgM, but these are significantly less sensitive than rRT-PCR during acute infection. 6,7 Testing for anti-YFV IgM is often limited to reference laboratories. For both DENV and YFV, IgM is not reliably detectable until 5 days after symptom onset, and significant cross-reactivity occurs between flaviviruses.…”
mentioning
confidence: 99%
“…14,15,17 The POCKIT DENV assay demonstrated a sensitivity of 87.2% and detected 96.2% of DENVpositive samples with viral loads ³ 4.0 log 10 copies/mL. Viral loads in this range are common among patients who present within the first 5 days of symptom onset, 7 such that assay use could be targeted to a high-yield population based on information that is readily available at presentation. Notably, sensitivity is higher than that of a rapid NS1 assay used to test patients in Paraguay (71.4%).…”
mentioning
confidence: 99%
See 1 more Smart Citation